Stakeholder-Engaged Research: What Our Friendship in Aphasia Team Learned About Processes and Pitfalls. Issue 1 (January 2023) - Strong, Katie A.; Douglas, Natalie F.; Johnson, Rebecca; Silverman, Maura; Azios, Jamie H.; Archer, Brent
Abstract : There is a need for intervention to support friendship for people living with aphasia. The purpose of this article is to describe a stakeholder engagement process that involved researchers, clinicians, people living with aphasia, and care partners to inform such intervention. Through reflection and firsthand accounts of non–university-based researchers, people not typically represented in the research process, we share details of two main lessons learned throughout the stakeholder engagement journey: (1) accessible engagement and (2) team correspondence. Finally, we describe experiences with use of the Social Convoy Model to support discussion and engagement about friendship and aphasia. We argue that this tool be a consideration in future intervention research in this area to support people with aphasia communicating their friendship priorities and goals. Although the richness of multistakeholder research teams has been documented, we hope that this article provides detail that is not commonly shared thus illuminating the process. We also hope to provide a transparent account of the cost and time required to ensure equity across stakeholder groups.